How do interpreters become heroes? Narratives on Soviet/Russian military interpreters - Probirskaja, Svetlana (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
This article identifies narratives, or storylines, which represent Soviet/Russian wartime/military interpreters. The data include the autobiographical writings of interpreters, documentaries, media articles, scholarly articles, and websites. The examination of the data proceeds to some extent in accordance with the narrative typology provided by Mona Baker (2006), that is, from general to personal narratives, with the assumption that personal narratives are embedded in collective narratives. The positioning of wartime interpreters participating in the Great Patriotic War (1941–1945) is compared to that of military interpreters participating in the military operations of the Soviet Union in the 1970s and 1980s. A narrative reading of the data uncovers the storylines that portray wartime/military interpreters as quiet war heroes.